Uncertainty quantification for a sailing yacht hull, using multi-fidelity kriging. (21st December 2015) - de Baar, Jouke; Roberts, Stephen; Dwight, Richard; Mallol, Benoit
Highlights: We simulate the flow around a sailing yacht hull. We use multi-fidelity Kriging to combine simulations on different spatial grids. This enables us to propagate parameter uncertainty at relatively low computational cost. We compare our results with experimental data. Based on the experimental data, we estimate the input parameters. Abstract: Uncertainty quantification (UQ) for CFD-based ship design can require a large number of simulations, resulting in significant overall computational cost. Presently, we use an existing method, multi-fidelity Kriging, to reduce the number of simulations required for the UQ analysis of the performance of a sailing yacht hull, considering uncertainties in the tank blockage, mass and centre of gravity. We compare the UQ results with experimental values.